Palavras em p-e-d-a-ç-o-s - Branco, Vanessa Goulart (2021)
This research deals with the vocal expression of words, based on the segmentation perspective. The study starts from the observation of the way students operate with the language during the vocalization of segmented words in a municipal co ntest held in the city of Lages/SC, in 2019. The investigation is justified by the attempt to analyze the linguistic aspects of said contest within a Saussurian perspective, with the aim of understanding the relationship between the process of vocalization and the segmentation of words, taking into account the linguistic phenomena involved in this process. Therefore, this work starts from the reflection about the main Saussurian concepts, namely: language, language and speech; linguistic sign (value, arbitrariness and linearity); delimitation of units; analogy; phonology; and written, in order to account for the analysis of the object of study. In this way, the research is methodologically characterized as exploratory, bibliographic and qualitative, since it is based on a bibliographic review and on the analysis of excerpts from recordings during the final spelling bee. For that, eighteen scenes were selected in which the request made by the students for the repetition of the word, the meaning or application in the sentence; the intonation; the vocalization of certain phonemes; the sequence of the spelled letters; and the facial or body expression during vocalization were observed. Therefore, the analysis and description of the scenes are presented in the light of theoretical concepts arising from Saussure's thought. The analysis shows that the vocalization of segmented words results from a process of complex operations of students with the language in search of meaning (s), so it is not a mechanical process of memorization or mere exercise of expression of vocal figures.